Analysis of compliance issues and influencing factors in the management of BSL-2 laboratories for pathogenic microorganisms in Lishui, China - Cong, Ying; Li, Jinkai; Lou, Dingshuo; Zhu, Jianliang; Zhang, Deyong; Cheng, Dongqing; Chen, Xiuying (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe management of biosafety laboratories for pathogenic microorganisms is directly related to public health and the effectiveness of biological experiments. However, persistent non-compliance issues in biosafety level 2 (BSL-2) laboratory management remain a challenge. This study aimed to assess the quality control of BSL-2 laboratories for pathogenic microorganisms in Lishui.MethodsBy combining the Biosafety Online Supervision Systems and on-site inspections, this study assessed the quality control of 73 medical institutions and the 128 biosafety laboratories under their management in Lishui.ResultsThe results discovered that the 73 medical institutions had low compliance rates in several fields: Responsibilities of the biosafety management (80.82%), development of system documentation (65.75%), risk assessment (84.56%), training of laboratory personnel (82.19%), and biosafety labeling (52.05%). Additionally, 128 laboratories had low pass rates for the access control management system (85.94%), hand/eye wash and shower stations (85.94%), and biosafety cabinet operations (89.06%).ConclusionThis study demonstrates that future efforts should focus on strengthening laboratory personnel training and implementing biosafety management responsibilities to ensure safe and regulation-compliant operations in laboratories handling pathogenic microorganisms.